Ectopic production of human chorionic gonadotropin in transitional cell carcinoma of the bladder. An immunohistochemical study - (:unkn) unknown (My University, 1990)
A retrospective histopathological and clinical analysis of 43 patients with transitional cell carcinoma of the bladder, attending our institution between March 1986 and April 1989, was performed. The indirect immunoperoxidase method was used for the demonstration of human chorionic gonadotropin production in transitional cell carcinoma cells. Nine of the 16 grade III tumors stained positive for human chorionic gonadotropin, while grade I and grade II tumors remained unstained. Our results suggest that the presence of human chorionic gonadotropin in tumor cells is a strong evidence of dedifferentiation, and its association with patient prognosis needs further investigation, especially in high-grade, low-stage tumors.
Keywords: Bladder carcinoma; Human chorionic gonadotropin; Immunohistochemistry